The Meaning of Bahr in the Qur’an: Semantic Analysis by Toshihiko Izutsu : (Arti Bahr dalam Al-Qur'an: Analisis Semantik oleh Toshihiko Izutsu) - Hidayah, Afita Nurul; Setiawan, Agus; Farhati, Wahdah; Arifin, Ali Zaenal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
The Qur’an often employs words that appear to be synonyms but have subtle differences in meaning. Such is the case with the use of the terms bahr and yamm for the sea. This study explores why the Qur’an uses bahr in certain cases and yamm in others, with the hope of discovering the semantic meaning of bahr and its implications on the concept of mutaradif (synonyms) in the Qur’an. The inquiry is particularly relevant today, as the sea—an essential part of human life—is facing ecological dangers wrought by human actions. Adopting a qualitative library-research design, data were gathered from Qur’anic verses containing bahr yamm, classical and modern Arabic lexicons, and major tafsir works; analysis followed Izutsu’s semantic procedures (syntagmatic–paradigmatic mapping, synchronic–diachronic tracing, and worldview synthesis), with validity strengthened through source triangulation and peer/expert review. Using Toshihiko Izutsu’s semantic theory, this research analyzes the term bahr to identify its hidden meanings and its theological and ethical implications. Findings indicate a deliberate lexical differentiation: bahr extends beyond the physical sea toward divine taskhir, order, and benefit, whereas yamm appears predominantly in threat–punishment narratives. Taken together, the Qur’an does not employ near-synonyms interchangeably; this contrast clarifies Qur’anic diction and underpins a theological–ecoethical call to gratitude, restraint and responsible marine stewardship.